Ewolucja gminy w Rzeczypospolitej Polskiej – zarys problematyki - Behr, Jolanta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The subject of this article is the commune in the Republic of Poland. The commune is part of public administration, which is based on the principle of decentralization. The aim of the following work is to present the commune as a subject that has been created in an evolution process. Proposing this thesis in the article is a justification for the use of historical methodology, consisting in analyzing the evolution process of an institution and searching for concrete causality. The main methodology used in this work is based on the textual analysis of legal acts. Moreover, the specific solutions are analyzed in the context of their historical situations. The deliberations are chronologically limited from the creation of the II Republic of Poland in 1918 to analyzing current legal acts. Comparison of the aforementioned regulations leads to the conclusion that the commune system from the II Republic of Poland shows many resemblances to the commune system in the III Republic of Poland. Considerations also lead to the conclusion about consistency of thought related to the position of the commune and its function.
Keywords: history; Poland; commune; creation; autonomy; decentralization; evolution; local government